Dirt on my diamonds. Volume 1 [compact disc] - Shepherd, Kenny Wayne (Provogue Records, 2023)
Hot on the heels of his critically acclaimed 2022 re-issue, Trouble ls...25', Shepherd returns with a new project that builds upon his already legendary repertoire. Three decades since the release of his debut album, 1995's Ledbetter Heights, this Grammy-nominated, multi-platinum bandleader still sounds like the future of the blues. If you approach this album expecting autopilot twelve bars, then you'll be thrown a volley of curveballs in the best way possible. With material this strong, no polish was needed. As on any KWS album, songs are the currency, and the seven originals from demand to be heard, lifting listeners above their circumstances at a time when life often feels bleak and bone raw.